Envisioning the future, conceptualising public space: Hanoi and Singapore negotiating spaces for negotiation - Anna-Katharina Hornidge; Sandra Kurfürst (University of Bonn, Center for Development Research (ZEF), 2010)
Southeast Asia, former battleground of opposing ideologies, is increasingly turning to market liberalisation; in Vietnam the vision of a 'socialist-oriented market economy', in Singapore of a 'knowledge society' is pursued. This paper assesses these visions' influence on the local conceptualisations of public space. On Ba Dinh Square/Hanoi, official space is transformed into concrete public space through citizens' negotiation. In Singapore's libraries, the aim to foster knowledge production and creativity results in the construction of spaces for collaborative learning and discussions. Consequently this paper studies the political balancing act between tolerating the voicing of public opinions and upholding authoritarian governance practices by focussing on the conceptualisations of physical and institutional public space and their role in redefining social order.
Keywords: 330; Vietnam; Singapore; Public Space; Knowledge-based Economy; Socialist-oriented Modernisation